The Seven Earths and Seven Heavens in the Light of Jung, Maslow and Hindu Psychology - Bharat Jhunjhunwala (University of Tabriz, 2021)
The Holy Quran tells of Allah creating seven heavens and seven earths. These have been traditionally identified cosmologically with seven stars etc. or geographically with seven lands. We provide an alternative interpretation that these refer to seven centers in the spinal cord. Each center has a physical location and a psychic quality. Abraham Maslow has suggested that a human being evolves progressively through seven needs. We suggest this evolution refers to the consciousness of a person rising thorugh the seven centers in the spinal cord. Car G. Jung has commented on the Hindu understanding of these seven centers and endorsed that these have psychic qualities. We find that this understanding is consistent with the Quran. In particular, a Hadith tells of the area from the Prophet’s “throat to lower part of the abdomen” being washed. This is the location of the lower five of the seven psychic centers in the spine. The Hadith then goes on to tell that the Prophet ascended the seven heavens and met with Adam, Jesus and John, Joseph, Idris, Aaron, Moses and Abraham sequentially. In the seventh heaven He was shown Bait-al-Ma'mur or Allah's House which could indicate that his consciousness reached the crown center which is said to be the seat of “spiritual emancipation.”